Unlocking motor reserve: behavioral and neuroimaging correlates of locomotor adaptability from youth to old age - Kögler, Stefanie; Hiew, Shawn; Peach, Robert; Schindehütte, Magnus; Pham, Mirko; Nguemeni, Carine; Zeller, Daniel (Frontiers in Systems Neuroscience, 2025)
BackgroundAging humans show a remarkable heterogeneity in agility, dexterity, and mobility. Once motor functions are impaired, their restoration may be challenging or even impossible. Thus, it is crucial to anticipate and address declines in mobility due to age- and disease-related reductions in cognitive and motor resources. Quantification of the individual motor adaptive capacity, or “motor reserve” (mR), is essential for the development of innovative treatments enhancing this reserve.ObjectiveTo assess whether biographical, behavioral, and neuroimaging measures can serve as quantifiable indicators of mR.MethodsTwenty-four healthy adults aged 21–80 years underwent cross-sectional assessment. Adolescent and recent physical activity was gathered via questionnaires. Current adaptability was investigated using a locomotor adaptation task on a split-belt treadmill and a visuomotor adaptation hand task. Magnetic resonance imaging (MRI) was used to assess grey matter volume and resting-state functional connectivity in motor and locomotor brain centres.ResultsAs expected, six-minute walking distance declined with age, largely reflecting reductions in grey matter volume. In contrast, motor adaptation abilities were preserved across the age span. Locomotor adaptation rates were positively associated with structural and functional integrity of motor networks, which were, in turn, influenced by long-term physical activity.ConclusionVariability in motor adaptability among older adults may be explained by individual differences in motor network integrity and lifelong physical activity. The findings of this exploratory cross-sectional study support the potential of MRI-based connectivity measures and locomotor adaptation performance as surrogate markers of motor reserve. Enhancing mR through targeted interventions may help sustain mobility and functional independence in aging populations.